Production and Characterization of Pulchellin A chain conjugated to HIV mAbs, and study its selective cytotoxicity against cells expressing HIV envelope - Sadraeian, Mohammad (2017)
Immunotoxins (ITs), which consist of antibodies conjugated to toxins, have been proposed as a treatment for cancer and chronic infections. To develop and improve the ITs, different toxins such as ricin, have been used, aiming for higher efficacy against target cells. The toxin pulchellin, isolated from the Abrus pulchellus plant, has similar structure and function as ricin. Here we have compared two plant toxins, recombinant A chains from ricin (RAC) and pulchellin (PAC) toxins, for their ability to kill HIV Env-expressing cells. Briefly, RAC and PAC were produced in E. coli, and chromatographically purified, then chemically conjugated to two different anti-HIV monoclonal antibodies (MAbs), anti-gp120 MAb 924 or anti-gp41 MAb 7B2. These conjugates were characterized biochemically by microcapillary electrophoresis and BCA assay and immunologically by a variety of ELISA tests. We performed a side-by-side comparison of their ability to bind, enter and kill HIV infected cells (H9/NL4-3) or Env-transfected 293T cells, as well as their non-specific toxicity on uninfected or non-transfected parental cells. Cell binding and internalization were studied by flow cytometry and confocal microscopy. Results showed that PAC can function within an effective IT. The ITs demonstrated specific binding against native antigens on persistently HIV-infected cells and recombinant antigens on Env-transfected cells. An irrelevant antibody conjugated to either RAC or PAC had no effect. PAC cytotoxicity appears somewhat less than RAC, the standard for comparison. This is the first report that PAC may have utility for the design and construction of therapeutic ITs, highlighting the potential role for specific cell targeting not only for AIDS also for cancer therapy.